Reconstructed Light Extinction Coefficients Using Chemical Compositions of PM_（2.5） in Winter in Urban Guangzhou, China - 陶俊 曹军骥 张仁健 朱李华 张涛 施思 陈尊裕 (大气科学进展：英文版, 2012)
The objective of this study was to reconstruct light extinction coefficients （b ext ） according to chemical composition components of particulate matter up to 2.5 μm in size （PM 2.5 ）. PM 2.5 samples were collected at the monitoring station of the South China of Institute of Environmental Science （SCIES, Guangzhou, China） during January 2010, and the online absorbing and scattering coefficients were obtained using an aethalometer and a nephelometer. The measured values of light absorption coefficient by particle （b ap ） and light scattering coefficient by particle （b sp ） significantly correlated （R 2 0.95） with values of b ap and b sp that were reconstructed using the Interagency Monitoring of Protected Visual Environments （IMPROVE） formula when RH was 70%. The measured b ext had a good correlation （R 2 0.83） with the calculated b ext under ambient RH conditions. The result of source apportionment of b ext showed that ammonium sulfate [（NH 4 ） 2 SO 4 ] was the largest contributor （35.0%） to b ext , followed by ammonium nitrate （NH 4 NO 3 , 22.9%）, organic matter （16.1%）, elemental carbon （11.8%）, sea salt （4.7%）, and nitrogen dioxide （NO 2 , 9.6%）. To improve visibility in Guangzhou, the effective control of secondary particles like sulfates, nitrates, and ammonia should be given more attention in urban environmental management.